3D Printed Biocompatible Enclosures for an Implantable DBS Microdevice. (2015) - Adams, Scott; Kouzani, Abbas Z.; Mohammed, Mazher; Usma, Clara; Tye, Susannah J.
Abstract: A number of methods have been used to make electronic medical microdevices biocompatible. This paper presents a novel approach for design and fabrication of biocompatible silicone enclosures for implantable medical microdevices. The approach involves design and formation of a 3D model of the enclosure using a computer-aided design software tool, followed by 3D printing of the enclosures using a bioplotter. Three different implantable enclosure designs are presented. The fabrication of the three enclosures is given. An evaluation of the suitability of the enclosures for implantation of a deep brain stimulation microdevice is discussed through submersion and operation tests. The evaluation results are presented and discussed.